2013
DOI: 10.3389/fnins.2012.00194
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Receptors, and Attachment: A Review of Individual Factors Influencing Response to Oxytocin

Abstract: As discussed in the larger review in this special issue (MacDonald and Feifel), intranasal oxytocin (OT) is demonstrating a growing potential as a therapeutic agent in psychiatry. Importantly, research suggests that a variety of individual factors may influence a person’s response to OT. In this mini-review, I provide a review of three: (1) sex and hormonal status; (2) genetic variation in aspects of the OT system (i.e., OT receptors); and (3) attachment history. Each of these factors will be important to moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
96
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 146 publications
10
96
0
2
Order By: Relevance
“…This raised the question whether and how the current effect can be generalized to other populations. Previous studies have shown differential or even opposing oxytocin effects between males and females (Macdonald, 2012;Fischer-Shofty et al, 2013;Rilling et al, 2014). Gender differences were also observed in ingroup favoritism (van Vugt et al, 2007;Charness and Rustichini, 2011).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This raised the question whether and how the current effect can be generalized to other populations. Previous studies have shown differential or even opposing oxytocin effects between males and females (Macdonald, 2012;Fischer-Shofty et al, 2013;Rilling et al, 2014). Gender differences were also observed in ingroup favoritism (van Vugt et al, 2007;Charness and Rustichini, 2011).…”
Section: Discussionmentioning
confidence: 51%
“…Participants were instructed to refrain from smoking or drinking (except water) for 2 h before the experiment. Previous studies reported gender differences in both oxytocin function (Macdonald, 2012;Fischer-Shofty et al, 2013;Rilling et al, 2014) and ingroup favoritism (van Vugt et al, 2007;Charness and Rustichini, 2011). In addition, studies examining oxytocin effects on social cognition and behaviors have been conducted mainly with men (van IJzendoorn and Bakermans-Kranenburg, 2012).…”
Section: Participantsmentioning
confidence: 99%
“…From a neuroendocrine perspective, oxytocin is known to be an important mediator of social behavior and emotional recognition, and an improvement in behavior in bvFTD patients has been suggested with administration of oxytocin [44]. Oxytocin through interactions with gonadal hormones has also been suggested to affect sexual function [45], with decreased levels or action potentially producing decreased sexual drive. When bvFTD patients are administered oxytocin a proportion develop hypersexual behavior [46].…”
Section: Discussionmentioning
confidence: 99%
“…A ocitocina (OT) é um hormônio peptideo liberado pela neurohipófise relacionada a uma ampla variedade de efeitos fisiológicos centrais e periféricos (SHEPARD et al, 2009;FELDMAN;VIERO et al, 2010;GORDON et al, 2011;EBSTEIN et al, 2012;FELDMAN, 2012;LOPATINA et al, 2012;CARSON et al, 2013 1 ), influenciando em diversos níveis na reprodução de todos os vertebrados (ANOUAR et al, 1996;OSTROWSKI, 1998;INABA et al, 1999;GIMPL;FAHRENHOLZ, 2001;FILIPPI et al, 2002;THACKARE;WHITTINGTON, 2006;VIERO et al, 2010;DEBLON et al, 2011;GARRISON et al, 2012;MACDONALD, 2012). Este hormônio exerce um papel fundamental na contração do miométrio no momento do parto e na contração das células mioepiteliais da glândula mamária permitindo a ejeção do leite e lactação, apresentando receptores que circundam os alvéolos e ductos mamários (ANOUAR et al, 1996;FUCHS et al, 1996;REZAPOUR;BACKSTROM;ULMSTEN, 1996;ZINGG, 1996;IVELL, 1997;KIMURA et al, 1998;INABA et al, 1999;BAE;WATSON, 2003;THACKARE;WHITTINGTON, 2006;PRETZER, 2008;LEE et al, 2009;GORDON et al, 2010;LUI et al, 2010;DEBLON et al, 2011;MAGON;…”
Section: Introductionunclassified
“…Outras funções da OT incluem os efeitos no sistema cardiovascular (HATAMI;VALOJERDI;MOWLA, 2007;AHMED;ELOSAILY, 2011;LOPATINA et al, 2012), a regulação da proliferação celular em diferentes tecidos (PETERSSON et al, 2002;HATAMI;VALOJERDI;MOWLA, 2007;SENDEMIR et al, 2008;ZHONG et al, 2010;VRACHNIS et al, 2011), e os efeitos no sistema nervoso central relacionados ao aprendizado, memorização, estresse, desordens neuropsiquiátricas, tendo um papel chave no comportamento social e relacionamento entre os mamíferos (OSTROWSKI, 1998;UVNAS-MOBERG et al, 2001;PRETZER, 2008;SHEPARD et al, 2009;YOUNG, 2009;GORDON et al, 2010;BOWEN et al, 2011;CHEN et al, 1,2 CARSON, D. S.; GUASTELLA, A. J.; TAYLOR, E. R.; MCGREGOR, I. S. A brief history of oxytocin and its role in modulating psychostimulant effects. Journal Psychopharmacology, GORDON et al, 2011;MAGON;KALRA, 2011;TOPS et al, 2011;EBSTEIN et al, 2012;FELDMAN, 2012;LOPATINA et al, 2012;MACDONALD, 2012;POULIN;HOLMAN, 2013 3 ; POURNAJAFI-NAZARLOO et al, 2013 4 ).…”
Section: Introductionunclassified